Utilization of Alice Software in Teaching Programming Language - Ceren Baştemur Kaya; Hasan Çakır (Anı Publishing, 2018)
Learning a programming language is a difficult and complicated process. It has been seen that the use of visualization tools has increased to decrease the complexity of learning programming. One of the visualization tools used for this purpose is Alice software. This study investigates the use of Alice software in learning Java programming language. The study group consists of 20 students who study at the 2nd year of vocational schools, department of computer technologies. The study was carried out five weeks to be four hours in a week and it was applied for 20 hours in total. The courses were realized using Gagne's nine events of instruction model. Reflections were collected from the students in every other week. Descriptive case study method was utilized in the study and the data were analyzed using content analysis method. When the results were examined, it is seen that the students have stated that the computers freeze due to the high hardware requirements of the Alice program. Despite that, It is observed that Alice program helped learning the coding logic, increased interest in programming and made programming fun. It is thought that use of Alice software can be beneficial for better understanding of programming logic.